1975
DOI: 10.1084/jem.141.6.1249
|View full text |Cite
|
Sign up to set email alerts
|

The mediator of cellular immunity. IX. The relationship between cellular hypersensitivity and acquired cellular resistance in rats infected with Listeria monocytogenes.

Abstract: Acquired resistance to the intracellular bacterial parasite, Listeria monocytogenes can be transferred to normal recipients by thoracic duct lymphocytes or peritoneal exudate cells obtained from rats infected with this organism; The appearance of protective cells in thoracic duct lymph coincides with the development in the donors of delayed-type hypersensitivity to Listeria antigens and accumulation in induced peritoneal exudates of cells which are responsive to these antigens in the migration inhibitory facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The fact that a single exposure to UV radiation induces a systemic alteration in antigenpresenting cell function (Noonan et a!., 1981a) is consistent with this contention. The direct correlation between generation of DTH and the resistance to infection with Herpes simplex virus (Schrier et al, 1982;Nash and Gell, 1983), Listeria monocytogenesb (Kostiala and McGregor , 1975), Leishmania tropica (Howard et al, 1980), and, of course, Mycobacterium tuberculosis are a few examples of the link between the DTH respnse and host resistance against microbial pathogens. The fact that a single exposure to UV radiation can suppress the DTH response to complex antigens suggests that exposure to UV radiation might also have the potential to interfere with the immune response to pathogenic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that a single exposure to UV radiation induces a systemic alteration in antigenpresenting cell function (Noonan et a!., 1981a) is consistent with this contention. The direct correlation between generation of DTH and the resistance to infection with Herpes simplex virus (Schrier et al, 1982;Nash and Gell, 1983), Listeria monocytogenesb (Kostiala and McGregor , 1975), Leishmania tropica (Howard et al, 1980), and, of course, Mycobacterium tuberculosis are a few examples of the link between the DTH respnse and host resistance against microbial pathogens. The fact that a single exposure to UV radiation can suppress the DTH response to complex antigens suggests that exposure to UV radiation might also have the potential to interfere with the immune response to pathogenic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators found a positive correlation between DTH and specific acquired resistance (ACR) against the infection with Listeria monocytogenes [12,15,16,21]. shows that the elimination of Listeria from infected sites was accelerated by the transfer of Listeria-irnmune serum, whereas immunization alone, without serum transfer, was not effective, compared with non-immune normal mice at 24 h after bacterial rechallenge.…”
Section: Augmentation Of Acquired Resistance To Local Infection Of LImentioning
confidence: 99%
“…This factor, DTH-augmentation factor (DAF) was produced or secreted by T ceils, and acts on the induction phase of DTH, antigen-specifically: It is important to elucidate whether this kind of factor participates in the establishment of DTH to various Offprint requests to: A. Yamada kinds of antigens. Such cellular resistance correlates with DTH to this bacterial antigen and is considered to depend on the cooperation between sensitized T lymphocytes and macrophages [12,15,16]. Resistance to facultative intracellular bacteria such as Listeria monocytogenes is mediated by cellular but not by humoral immunity [ 13,15,18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that immunologically mediated resistance to infection occurs when Listeriaimmune T cells stimulated by Listeria antigens release lymphokines which non-specifically activate macro phages to eliminate intracellular Listeria. Indeed, it has been demonstrated that Lis/eria-immune T cells can release migration inhibition factor (MIF) [12,13] and mitogenic protein [14], However, since Listeria derived components are also B cell mitogens and po lyclonal activators [5][6][7], and since B cells can some times release lymphokines when stimulated by mito gens and antigens [1][2][3][4], it was important for an un- derstanding of cellular events in resistance to listerio sis to determine whether B cells stimulated with Liste ria-derived materials could also release lymphokines. Thus, the experiments reported here demonstrate that Li.v/erta-immune T cells, stimulated with Listeria anti gens could release MIF, but that neither Listeria-im mune nor normal B cells, stimulated with Listeria an tigens or B cell mitogens, could release MIF.…”
Section: Introductionmentioning
confidence: 99%